2001
DOI: 10.1152/ajpcell.2001.281.2.c563
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK mediates renal tubular cell TNF-α production and TNF-α-dependent apoptosis during simulated ischemia

Abstract: Ischemia causes renal tubular cell loss through apoptosis; however, the mechanisms of this process remain unclear. Using the renal tubular epithelial cell line LLC-PK(1), we developed a model of simulated ischemia (SI) to investigate the role of p38 MAPK (mitogen-activated protein kinase) in renal cell tumor necrosis factor-alpha (TNF-alpha) mRNA production, protein bioactivity, and apoptosis. Results demonstrate that 60 min of SI induced maximal TNF-alpha mRNA production and bioactivity. Furthermore, 60 min o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 56 publications
2
73
0
Order By: Relevance
“…It was reported that elevated plasma levels of inflammatory cytokines were related to heart dysfunction (Chen et al 2003;Meldrum et al 2001;Peng et al 2003). Previous studies have accumulated much evidence that the changes of inflammatory cytokines, such as some TNF-a and IL-6, plays an important role in the process of pathological heart remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that elevated plasma levels of inflammatory cytokines were related to heart dysfunction (Chen et al 2003;Meldrum et al 2001;Peng et al 2003). Previous studies have accumulated much evidence that the changes of inflammatory cytokines, such as some TNF-a and IL-6, plays an important role in the process of pathological heart remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, p38 MAPK-mediated inhibition of TNF-a expression was reported during simulated ischemia (Meldrum et al 2001). Furthermore, it was reported in renal tubular cell activation of p38 MAPK enhances TNF-a secretion and induced apoptosis (Meldrum et al 2001). These observations led us to hypothesize that TNF-a and p38 MAPK are mutual activated through oxidative stress-induced pathways in cardiac cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, dilated tubules in diabetic kidneys appeared to have an increased proportion of p-p38+ cells, suggesting that increased phosphorylation of tubular p38 also occurs in response to tubular injury. Phosphorylation of p38 in tubular cells can, in turn, promote production of TNF-α and epithelial transdifferentiation into myofibroblasts [40,41], which can subsequently increase interstitial inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ is produced by the kidney after renal ischemia in vivo (see review, reference 9) and by hypoxic LL-CPK 1 renal tubule cells in vitro (10). Injury is ameliorated by TNF-␣ receptor antagonists (11) or anti-TNF-␣ monoclonal antibodies (12).…”
mentioning
confidence: 99%